2015
DOI: 10.1039/c5cp04505c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the fundamentals of redox mediators in Li–O2 batteries: a case study on nitroxides

Abstract: The development of aprotic lithium-oxygen (Li-O2) batteries suffers from high charging overvoltages. Dissolved redox mediators, like nitroxides, providing increased energy efficiency and longer lifetime are promising tools to overcome this challenge. Since this auspicious concept is still in its infancy, the underlying chemical reactions as well as the impact of the different (electro)chemical parameters are poorly understood. Herein, we derive an electrochemical model for the charging reactions, which is vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 47 publications
2
110
0
3
Order By: Relevance
“…Av ariety of organic, organometallic,a nd inorganic compounds have been identified as OERMs. [77] Organic OERMs such as TTF [72,78] and tetramethylpiperidinyloxyl (TEMPO) [79][80][81] are molecules with double bonds and/or an aromatic nature which undergo redox reactions through electron exchange of noncovalent/resonance structures. Their electronic structures strongly determine the redox potentials;therefore,alarge number of organic materials can be designed to fulfill the requirements of OERMs.Ionization energy is an important parameter, according to which possible rules for the design of organic OERMs have been proposed.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Av ariety of organic, organometallic,a nd inorganic compounds have been identified as OERMs. [77] Organic OERMs such as TTF [72,78] and tetramethylpiperidinyloxyl (TEMPO) [79][80][81] are molecules with double bonds and/or an aromatic nature which undergo redox reactions through electron exchange of noncovalent/resonance structures. Their electronic structures strongly determine the redox potentials;therefore,alarge number of organic materials can be designed to fulfill the requirements of OERMs.Ionization energy is an important parameter, according to which possible rules for the design of organic OERMs have been proposed.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Bergner et al. systematically investigated the typical representatives of different nitroxide subgroups and found that all nitroxide radicals can greatly reduce the charge overpotential, some of which can directly affect the discharge process …”
Section: Redox Mediators For Chargementioning
confidence: 99%
“…When used in Li−O 2 batteries, redox mediators electrochemically oxidize firstly in the charging process, and then chemically oxidize Li 2 O 2 to release O 2 . With the aid of redox mediators, such as tetrathiafulvalene (TTF), 2,2,6,6‐tetramethylpiperidinyloxyl (TEMPO), tri[4‐(diethylamino)phenyl]amine (TDPA), 10‐methylphenodiazine (MPT), and lithium bromide (LiBr), the discharge products would be decomposed easily and completely, as the overpotential could be reduced to a great extent. In rechargeable Li−CO 2 batteries, the discharge products are much more difficult to decompose even with the aid of electrocatalysts, and the accumulated insulating Li 2 CO 3 could increase the charging voltage and even the sudden death of batteries.…”
Section: Figurementioning
confidence: 99%